PENGARUH MORAL REASONING, RELIGIUSITAS, INDEPENDENSI, DAN SKEPTISISMA PROFESIONAL TERHADAP KUALITAS AUDIT AUDITOR PEMERINTAH - , ELY WINDARTI HASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to empirically examine the factors that affect the quality of the external auditors audit the Indonesian government. The object of this study is the auditor in Supreme Audit Agency that at least once had a position as Team Leader, Technical Controller, or a Quality Controller in an audit team. Data were collected using a questionnaire letter (mail-survey), which is distributed to the Provincial Legislative Audit Agency spread across the island of Sumatra, Java, and West Nusa Tenggara Province, amounting to 17 BPK. Of the 170 questionnaires distributed, only 97 were returned (57.06%) and only 74 questionnaires (78.72%) are eligible to be processed. The data is then analyzed using descriptive statistics, validity and reliability, as well as multiple regression test to test the hypothesis with the help of SPSS 19.0. The results of this study indicate that moral reasoning is not empirically proven to have a positive relationship with audit quality. The other variables such as independence and professional skepticisms proven empirically positively related to audit quality. Similarly, with the religiosity which is a new variable that is trying assessed its association with audit quality. The next study is expected to reexamine religiosity variable is a new variable, as well as re-testing instrument that audit quality is a new instrument for measuring the audit quality in the public sector, particularly the government sector in Indonesia.